Decenter Error Sensing Technology of Sparse Aperture Telescope Systems - Yang Liu; Haotong Ma; Bo Qi (IEEE Photonics Journal, 2021)
The imaging quality of sparse aperture telescope systems is degraded by several factors including design, manufacturing, and arrangement errors. To achieve a high-resolution, the optical system requires an accurate control of not only the wave-front errors such as the piston and tip-tilt but also the decenter errors. Decenter diminishes the field of view of synthetic systems heavily and causes frequency shifting as well. In this paper, we firstly present an approach to sense the decenter of the sparse aperture telescope using the multi-beam interference method based on phase shift and centroid extraction algorithm. The most attractive point of our method is that it can sense not only the decenter but also the other wave-front errors simultaneously, but does not need to install any additional sensors. The numerical simulations are described and preliminary experiments are performed for validation, demonstrating that this technique is efficient and accurate and could be used to guide future sparse aperture telescope error correction.